Coronal leakage of four intracanal medications after exposure to human saliva in the presence of a temporary filling material - Verissimo Rebeca; Gurgel-Filho Eduardo; De-Deus Gustavo; Coutinho-Filho Tauby; de Souza-Filho Francisco (Wolters Kluwer Medknow Publications, 2010)
Aim: To determine the time required for the recontamination of root canals medicated with four different materials. Materials and Methods: A total of 60 intact, caries-free, human single-rooted teeth with straight roots were selected for this study. After chemo-mechanical preparation they must be changed in the specimens into seven groups: 10 teeth medicated with calcium hydroxide (Ca(OH) 2) + Camphorated paramonochlorophanol (CPMC) (G.1); 10 medicated with 2.5% Sodium hypochlorite (NaOCL) (G.2); 10 medicated with 2% Chlorhexidine gluconate (CHX) in gel (G.3); 10 medicated with 2% CHX in gel + Ca(OH) 2 (G.4); 10 without intracanal medicament and sealed with a coronal temporary filling (G.5). Five teeth were without intracanal medicament and coronally unsealed, used as the positive control group (PC) (G.6) and 5 teeth with intact crowns used as the negative control group (NC) (G.7). Glass vials with rubber stoppers were adjusted for use. The medicaments were prepared and injected into the root canals using sterile plastic syringes. An apparatus was used to evaluate for 30 days leakage. The chamber was filled with 3 ml of human saliva and Brain Heart Infusion (BHI) broth, incubated at 37°C and checked daily for the appearance of turbidity in the BHI broth. Results: Recontamination was detected after an average time of 2.6 days in group 2, 15.9 days in group 3, 30 days in group 1, 27.6 days in group 4, 2.9 days in group 5, 1 day in the positive control, and there was no contamination in the negative control group. Conclusion : The NaOCl group showed the highest worst average of recontamination; on the other hand, high averages were also shown by Ca(OH) 2 + CPMC and Ca(OH) 2 + 2% CHX in gel.